Landfill site work performance based on residents perceptions of environmental impacts: case study in Malaysia - Nik Daud, Nik Norsyahariati; Aziz, Ruslina (Trans Tech Publications, 2012)
The disposal of solid waste using landfilling method has become a critical issue in Malaysia especially when concerning their impact towards environment. Eventhough the landfilling strategy applied in Malaysia is a very much improved version; gas and leachate produced from the landfill site still gave a major health issue to the existing residents. Thus, the work performance has been questioned. This paper presents a survey study of the environmental impacts to the nearby residents emerged from the landfilling activities at Jabi town, located in Kedah state, Malaysia based on their awareness and perceptions. Using the data collected, the work performance at site can be assessed. The landfill site has been categorised as a semi aerobic sanitary landfill. A self-administered questionnaire was used as a data collection tools. The level of severity has been determined using Severity Index method. From the discussions, the environmental impacts at specific site can be categorized as light problems and in a control condition. The work performance of selected landfill can be categorised as good due to the level of severity concluded.